1999
DOI: 10.1074/jbc.274.50.35483
|View full text |Cite
|
Sign up to set email alerts
|

The UDP-glucose:p-Hydroxymandelonitrile-O-Glucosyltransferase That Catalyzes the Last Step in Synthesis of the Cyanogenic Glucoside Dhurrin in Sorghum bicolor

Abstract: The final step in the biosynthesis of the cyanogenic glucoside dhurrin in Sorghum bicolor is the transformation of the labile cyanohydrin into a stable storage form by O-glucosylation of (S)-p-hydroxymandelonitrile at the cyanohydrin function. The UDP-glucose:p-hydroxymandelonitrile-O-glucosyltransferase was isolated from etiolated seedlings of S. bicolor employing Reactive Yellow 3 chromatography with UDP-glucose elution as the critical step. Amino acid sequencing allowed the cloning of a full-length cDNA enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
134
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 55 publications
3
134
0
Order By: Relevance
“…The protein extracts were subjected to immunoblotting and probed with a specific antibody against UGT85B1 (Jones et al, 1999). The immunoblotting analysis confirmed that each of the mutant proteins produced a discrete protein band with the expected M r .…”
Section: Biochemical Analysis Of Ugt85b1 Mutant Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…The protein extracts were subjected to immunoblotting and probed with a specific antibody against UGT85B1 (Jones et al, 1999). The immunoblotting analysis confirmed that each of the mutant proteins produced a discrete protein band with the expected M r .…”
Section: Biochemical Analysis Of Ugt85b1 Mutant Proteinsmentioning
confidence: 99%
“…Mandelonitrile was utilized as an acceptor molecule instead of p-hydroxymandelonitrile because mandelonitrile is more stable than p-hydroxymandelonitrile. UGT85B1 has previously been shown to glucosylate the two compounds at comparable rates (Reay and Conn, 1974;Jones et al, 1999). Product formation was assessed by thin-layer chromatography (TLC) and liquid chromatography-mass spectrometry (LC-MS) and showed that UDP-Glc, but not UDP-Xyl or UDP-GlcUA, served as sugar donors for UGT85B1 (Fig.…”
Section: Biochemical Assays With Udp Sugarsmentioning
confidence: 99%
See 3 more Smart Citations